2015
DOI: 10.1128/aem.01753-15
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Microbiota Progression from Calving until Establishment of Metritis in Dairy Cows

Abstract: The objective of this study was to evaluate the progression of the uterine microbiota from calving until establishment of metritis. Uterine swabs (n ‫؍‬ 72) collected at 0, 2, and 6 ؎ 2 days postpartum (dpp) from 12 metritic and 12 healthy cows were used for metagenomic sequencing of the 16S rRNA gene on the Illumina MiSeq platform. A heat map showed that uterine microbiota was established at calving. The microbiota changed rapidly from 0 to 6 ؎ 2 dpp, with a decrease in the abundance of Proteobacteria and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

27
186
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 145 publications
(220 citation statements)
references
References 25 publications
27
186
3
4
Order By: Relevance
“…Metritis was diagnosed by examining the uterine discharge from 92 cows at 4, 6, and 8 days postpartum (6 ± 2 DPP) using a 5-point scale as previously described [15]: 1 = not fetid normal lochia, viscous, clear, red, or brown; 2 = cloudy mucoid discharge with flecks of pus; 3 = not fetid mucopurulent discharge with < 50% pus; 4 = not fetid mucopurulent discharge with ≥ 50% pus; 5 = fetid red-brownish, watery discharge. Cows with a discharge score ≤ 4 were classified as healthy (n = 40) and cows with a score of 5 were classified as metritic cows.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Metritis was diagnosed by examining the uterine discharge from 92 cows at 4, 6, and 8 days postpartum (6 ± 2 DPP) using a 5-point scale as previously described [15]: 1 = not fetid normal lochia, viscous, clear, red, or brown; 2 = cloudy mucoid discharge with flecks of pus; 3 = not fetid mucopurulent discharge with < 50% pus; 4 = not fetid mucopurulent discharge with ≥ 50% pus; 5 = fetid red-brownish, watery discharge. Cows with a discharge score ≤ 4 were classified as healthy (n = 40) and cows with a score of 5 were classified as metritic cows.…”
Section: Methodsmentioning
confidence: 99%
“…Uterine swab samples from 12 cows that developed metritis but did not have a fever at the time of metritis diagnosis (MNoFever) were randomly selected for metagenomic sequencing. The 16S data for metritic cows with a fever (MFever; n = 11) and healthy cows (Healthy; n = 11) were obtained from a previous study [15], and were used as reference groups for comparison with the MNoFever group. In the previous study, 12 samples from MFever and 12 from Healthy cows had been randomly selected; however, one sample from each group failed to amplify.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, it was shown that species of the genus Sneathia have the potential to cause infections outside the reproductive tract due to their involvement in a case of septic arthritis (Bachy et al, 2011). Sequences associated with the genus Sneathia have also occasionally been reported as genital microbiota in cows and macaques (Hu et al, 2015;Jeon et al, 2015;Machado et al, 2012;Spear et al, 2012). Different growth characteristics, as well as preliminary molecular data, cast doubt over whether respective micro-organisms from guinea pigs are indeed affiliated to the genera Streptobacillus or Sneathia.…”
mentioning
confidence: 99%